The music man [videorecording (DVD)] - DaCosta, Morton, 1914-1989; Preston, Robert, 1918-1987; Jones, Shirley, 1934 March 31-; Hackett, Buddy, 1924-2003; Gingold, Hermione, 1897-1987; Ford, Paul, 1901-1976; Howard, Ron, 1954-; Willson, Meredith, 1902-1984 (Warner Bros. Entertainment : Distributed by Warner Home Video, 2010)
A con man in the guise of a traveling salesman gets off the train in River City, Iowa. He convinces the town to finance a children's marching band instead of a pool hall. Special features include: 'Right Here in River City' Documentary and Introduction by Shirley Jones.